Finite Element Simulation of Microfluidic Biochip for High Throughput Hydrodynamic Single Cell Trapping - Amelia Ahmad Khalili; Mohd Ariffanan Mohd Basri; Mohd Azhar Abdul Razak (Universitas Ahmad Dahlan, 2018)
In this paper, a microfluidic device capable of trapping a single cell in a high throughput manner and at high trapping efficiency is designed simply through a concept of hydrodynamic manipulation. The microfluidic device is designed with a series of trap and bypass microchannel structures for trapping individual cells without the need for microwell, robotic equipment, external electric force or surface modification. In order to investigate the single cell trapping efficiency, a finite element model of the proposed design has been developed using ABAQUS-FEA software. Based on the simulation, the geometrical parameters and fluid velocity which affect the single cell trapping are extensively optimized. After optimization of the trap and bypass microchannel structures via simulations, a single cell can be trapped at a desired location efficiently.